Deskripsi Peran Guru Dalam Membina Sikap Religius Siswa Sdn 1 Telaga Biru - Winda Farma Gana; Ansar Ansar; Thamrin Kum (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The purpose of this study is to examine the role of teachers in fostering religious attitudes among students at SDN 1 Telaga Biru. This study employed a descriptive qualitative method. Data were collected through observation, interviews, and documentation involving the Islamic Religious Education (PAI) teacher and the homeroom teachers of Grades IV and V. The findings indicate that teachers play three primary roles in cultivating students’ religious attitudes. First, as Mu’allim, teachers guide students by teaching religious values and integrating them into daily life. Second, as Mu’addib, teachers instill religious values by modeling exemplary behavior and serving as role models for their students. Third, as Mursyid, teachers provide continuous advice and reminders to encourage students to behave well and adhere to school rules. Overall, the study concludes that the development of students’ religious attitudes is carried out through three key approaches: habituation, exemplary behavior, and advisory guidance. It is recommended that efforts to foster students’ religious attitudes be carried out in collaboration with parents to ensure consistency between the school and home environment.